2021
DOI: 10.1016/j.critrevonc.2020.103174
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer, screening and diagnostic tools: All you need to know

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 392 publications
(615 reference statements)
0
37
0
1
Order By: Relevance
“…Once using an imaging technique an anomaly is found in the breast tissue, for diagnoses, prognosis and treatment purposes, cytological, histological and molecular analysis is applied to biopsies using genetic tests [gene sequencing and gene expression profiling signature (GEP/S) (28)(29)(30)] and biochemical markers (31)(32)(33)(34)(35). Biochemical markers can be found in tissues (31) and within the circulating blood (36) [e.g., circulating tumor cells (CTCs)]. Established biochemical biomarkers are proteins and comprise of ki6 7 (37), ER [ERa (38) and ERb (39)], PR (33) and HER2 (40).…”
Section: Introductionmentioning
confidence: 99%
“…Once using an imaging technique an anomaly is found in the breast tissue, for diagnoses, prognosis and treatment purposes, cytological, histological and molecular analysis is applied to biopsies using genetic tests [gene sequencing and gene expression profiling signature (GEP/S) (28)(29)(30)] and biochemical markers (31)(32)(33)(34)(35). Biochemical markers can be found in tissues (31) and within the circulating blood (36) [e.g., circulating tumor cells (CTCs)]. Established biochemical biomarkers are proteins and comprise of ki6 7 (37), ER [ERa (38) and ERb (39)], PR (33) and HER2 (40).…”
Section: Introductionmentioning
confidence: 99%
“…Further interdisciplinary studies in vivo or in patients will support the in silico role of the identified and overlapped proteins. Interdisciplinarity is important as it brings together specialists in bioinformatics, health care professionals and technical experts leading to the development of better screening methods for early diagnosis and therapies 106 . These studies would allow therapeutic targeting and the development of specific pharmacological compounds that would stop cancer progression without affecting the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…43 Screening programs for cancers like breast, cervix, and colorectum are established. [44][45][46] There are many established criteria for cancer screening. 9 The initial criteria were subsequently modified to bring in the more rigorous standards of evidence required to prove effectiveness, and the apprehensions about overdiagnosis resulting from false positive tests or lead time bias.…”
Section: Sensitivity Analysismentioning
confidence: 99%